2017
DOI: 10.1177/1087054717713639
|View full text |Cite
|
Sign up to set email alerts
|

Follow-Up of Young Adults With ADHD in the MTA: Design and Methods for Qualitative Interviews

Abstract: Qualitative methods captured the perspectives of YAs regarding using substances. This information is essential for improving resilience models in drug prevention and treatment programs and for treatment development for this at-risk population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(31 citation statements)
references
References 28 publications
2
29
0
Order By: Relevance
“…Also, they are consistent with the findings of the companion paper by Mitchell et al (in press), who addressed the topic of emotionality and marijuana in the excerpts from the M-EFI and reported that a higher percentage of ADHD than LNCG cases with Persistent SU perceived beneficial effects of marijuana use (improved negative mood; improved ADHD symptoms). Taken as a whole in the QIS, in the unconstrained narratives of the M-EFI, many of the ADHD cases expressed the belief that marijuana provides emotional “stability” and improves symptoms of ADHD (Weisner et al, under review; Mitchell et al, in press). This may reflect perceived self-medication of symptoms of ADHD and/or dysregulated mood.…”
Section: Discussionmentioning
confidence: 99%
“…Also, they are consistent with the findings of the companion paper by Mitchell et al (in press), who addressed the topic of emotionality and marijuana in the excerpts from the M-EFI and reported that a higher percentage of ADHD than LNCG cases with Persistent SU perceived beneficial effects of marijuana use (improved negative mood; improved ADHD symptoms). Taken as a whole in the QIS, in the unconstrained narratives of the M-EFI, many of the ADHD cases expressed the belief that marijuana provides emotional “stability” and improves symptoms of ADHD (Weisner et al, under review; Mitchell et al, in press). This may reflect perceived self-medication of symptoms of ADHD and/or dysregulated mood.…”
Section: Discussionmentioning
confidence: 99%
“…The remaining ADHD participants were recruited using random selection to obtain balanced representation across the four original treatment group assignments within each site; the remaining LNCG participants were randomly selected from the available pool of LNCG participants in the larger study. Only five potential qualitative interview study participants declined participation (see Weisner et al, in press, for more details)2w.…”
Section: Methodsmentioning
confidence: 99%
“…Please also note, given the ubiquity of SU/A experimentation among teens, “abstainers” included both youth who reported never using illicit drugs or heavy use of alcohol and youth who admitted to a single brief period of “experimentation,” followed by no subsequent periods of heavy use (see Weisner et al, in press, for further description of how “abstainers” were defined).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Whilst surveys and interviews can more directly interrogate the patient perspective and ensure that all participants have been diagnosed with ADHD (e.g. Weisner et al, 2018), social media analysis offers a complementary approach by investigating how people communicate about ADHD in an everyday setting.…”
Section: Introductionmentioning
confidence: 99%